PERAN ANTIOKSIDAN DALAM MENGATASI CEKAMAN KEKERINGAN PADA TANAMAN KEDELAI (Glycine max (L.) Merril) - Laily Asyura AG (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
The decreasing of soybean production full fill of soybean in Indonesia, one of the main causes is the decreasing of land farming area. To increase the production of soybean in Indonesia can be reached by the expansion of planting areas,use potential land. This research has held in plastic house Agriculture Faculty, University of Sumatera Utara, Medan on altitude +32 meters above sea level, to August 2016 until November 2016,using factorial rendomized block design with 2 factors.The first factor is drought stress with 3 levelsof KL 80% ; KL 60% ; KL 40% and the second factor is apllication antioxidants with 2 kind of Ascorbic Acid and Salicylic Acid.The result of this research showed that drought stresswere significantly effect to leaf area, the number of pods fullness per plant, dry weight of seeds per plant and dry weight of 100 seeds. Apllication antioxidantswere significantly effect to chlorophyll a, chlorophyll b, thenumber of pods fullness per plant, dry weight of seeds per plant and dry weight of 100 seeds.Interaction of drought stress and application antioxidant were significantly effect to dry weight of seeds per plant and dry weight of 100 seeds.